Plan de negocios para implementar una pastelería artesanal - Viza Tumbalobos, Javier Eduardo (2023)
This project aims the viability and profitability of implementing an artisanal pastry shop that initially caters to 7 and 8 zone in Lima. Through innovation and customization of the products, it aims to gain a place in the cake market, specifically in themed cakes. This idea stems from the desire to provide my mother with a proposal for the growth of her business. Currently, she has a small business dedicated to sell custom-made cakes, with clients usually being referred by other clients and with a limited production level. For this reason, the goal is to take the business to a more professional level with marketing campaigns on social media to penetrate the market, logistic strategies to reach customers more easily and be close to suppliers, cost optimization to maintain competitiveness, and pricing strategies to achieve significant profits in the large and divided cake market in Lima. Through a market investigation targeting individuals aged 25 to 65 in the districts of San Borja, Chorrillos, Barranco, San Isidro, Surquillo, La Molina, San Juan de Miraflores, Santiago de Surco, and Miraflores, the potential demand was calculated and with a financial analysis, the conclusion reached was that it is profitable and viable with potential for growth. Artesano Pastel aims to position itself as one of the best choices for trendy and innovative themed cakes in the chosen segment.